Avoiding pitfalls: Key insights and lessons learnt from customizing and rolling out a national web‐based system in Tanzania. Issue 6 (6th June 2021) - Sukums, Felix; Simba, Daudi; Kumalija, Claud; Asiimwe, Sarah; Pothepragada, Sai; Githendu, Patrick
Abstract: Tanzania is among the first countries to adopt District Health Information System version 2 (DHIS2) as the national health management information system (HMIS). In this article, we share experiences on achievements and challenges encountered in the process of customizing and rolling out the DHIS2 in Tanzania. This instrumental case study was conducted using a qualitative approach involving desk reviews, key informant interviews, and field observations. Tanzania successfully adopted the DHIS2 as evidenced by innovation of new apps; improving availability of quality data and enhancing data analysis. These achievements were attributed to inbuilt system strengths that provided the necessary flexibility for customization; the use of local experts to customize and maintain the system; cascaded training; and formation of a consortium to coordinate and support the rollout process. Prior existence of a robust paper‐based HMIS and lessons from other countries' experience favored smooth transition. However, several challenges hindered the DHIS2 implementation including donor dependency and ineffective cascade training that left many users untrained. Countries envisaging to adopt the DHIS2 need to consider the use of cost‐effective training approaches to accommodate all users including the use of champions to conduct on‐the‐job training, support, and mentoring.